Optimalisasi Pengetahuan Ibu Tentang Stunting Melalui Edukasi Kesehatan Berbasis Booklet - Erviana; Muhammad Taufik Page; Haryuni; Masniati; Irna Megawati (Institut Citra Internasional, 2025)
Lack of maternal knowledge can be one of the factors that can influence the incidence of stunting in children. One thing that can increase knowledge is by providing health education with booklet media. Booklet media is a small book size designed to provide education for readers in the form of strategies and tips for solving problems. The purpose of this study was to analyze the effectiveness of booklet media in increasing maternal knowledge about stunting in Tallu Banua village. The research method used in this study was a quasi-experimental design with a one group pretest-posttest design. The study population was mothers who had stunted children with a sample size of 32 people. The sampling technique used consecutive sampling. The analysis was carried out using the Marginal Homogeneity test. The results of the study showed that booklet media had an influence on increasing maternal knowledge where there was an increase in knowledge before and after being given education with booklet media with a p-Value of 0.000 (p <0.05). The conclusion in this study is that health education with booklet media is effective in increasing maternal knowledge about stunting.